Exploring the attractiveness of combinations of natural colors and contemporary shapes in fashion design - Krasimira Genova; Julieta Ilieva; Irina Ruseva; Liliana Doble; Gabriella Böhm; Zlatin Zlatev (Communications in Development and Assembling of Textile Products)
In this research, the attractiveness of combinations of natural colors and contemporary shapes in fashion design is explored. This was done by means of a questionnaire survey. Four shapes of clothing and ten colors obtained from plant and insect pigments are proposed. The research was conducted in two phases – qualitative and quantitative analysis. The quantitative study confirmed the results of the qualitative study and using an appropriate data reduction method, the study results were analyzed graphically. The results showed that users rated designs with high-contrast color and shape combinations as more attractive than those with low-contrast combinations. The study also showed that in addition to the shape of the garment, the choice of natural color sources can also influence consumer preferences. This study aims to overcome the shortcomings of previous studies that only examined color without investigating its relationship to garment shape. The knowledge gained from this study can help fashion designers create garments that are both aesthetically pleasing and environmentally friendly. However, further research is needed to determine the relationship between natural colors, contemporary shapes and consumer behavior in selecting them.